(untitled) (Research, Society and Development, 2022)
Bullying is a type of violent behavior that can be expressed in different ways, that is, through intentional, aggressive and repetitive attitudes adopted by one or more students against others who are unable to defend themselves. The study aimed to know the perception of elementary school teachers about bullying at school. A descriptive and exploratory qualitative research was carried out. Twelve elementary school teachers from a municipal school in a municipality in southern Brazil participated. Data were collected through interviews and submitted to Content Analysis. Data were obtained about the teachers’ perception about Bullying, the teachers’ experiences with Bullying, the teachers’ actions in the face of Bullying, the teachers’ preparation to act in the face of Bullying, the teachers’ perception of the causes that lead the aggressor to commit Bullying, the consequences of Bullying in the teacher’s perception, the role of the school in the face of Bullying in the teacher’s perception and the role of the family in the face of Bullying in the teacher’s perception. It was concluded that Bullying is a reality in schools. In this sense, teachers, school agents and families need to be guided on how to act to prevent and curb this type of action. School health nurses need to work with students, parents, teachers and school staff about what Bullying is and its consequences, and offer subsidies so that they can identify its signs and ways of approaching victims and aggressors.